Analisis Dan Perancangan Sistem Informasi Pelaporan Transaksi E-samsat Berbasis Web Pada PT. Bank Pembangunan Daerah Jambi - Maidoni, Fardinal; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2020)
PT. Bank Pembangunan Daerah Jambi collaboration with Jambi Government, PT. Jasa Raharja and Jambi Regional Police created an electronic vehicle tax payment service called E-Samsat. PT. Bank Pembangunan Daerah Jambi obliged to report E-Samsat transactions which received from the bank channels (ATM and mobile banking). E-Samsat transactions is reported manually, report is originated from transaction log and delivered to all parties via courier. This reporting make problems such as transaction differences and information delays. To solve this problems, researchers designed a web based E-Samsat transaction reporting information system. In design and analysis, researchers use UML method and design using prototype. Analysis and design produces useful features for all parties related to E-Samsat reporting such as E-Samsat transaction report management system integrated with bank channels, reporting feedback feature as material for review of reports submitted and real time information transaction. All features can be accessed easily because the system built via web based.